Gestão da coleta de resíduos sólidos na cidade universitária Prof. José da Silveira Netto da Universidade Federal do Pará - MACEDO, Silza Lena Fagundes (Universidade Federal do Pará, 2019)
Review the waste solid’s collection management in the Professor José da Silveira Netto’s University City at Federal University of Pará. In this research had been realized documentary surveys and field visits for analyze the operational diagnostic and costs from waste solids regular and selective collection; and verify the respect with Decree n. 5.940/2006 about selective collection in the public administration; then, propose actions for the waste solid’s collection management in the University City. The results obtained show the needs of register and systematization about information of volume and weight from waste solids related with operational’s sector, the combustive’s cost, vehicle’s maintenance and equipments of regular and selective collection costs spread sheet. Also had been verified the big proximity between total costs of regular collection (R$198.349,75) and selective (R$218.431,77) in this period: September 2013 and August 2014, although the weight of regular collection of 773.610 kg/year and the selective collection 172.584 kg/year. Relative the respect the law, is possible say UFPA created Selective Collection Commission, but it doesn’t attend the Decree 5.940/06, existing the needing of diverse actions, such as: infrastructure complementation and control/evaluation of Solidarity Selective Collection services. However, this work propose short, middle and large deadline for this actions, highlighting the needing for a big control of volume and costs related with waste collection’s services, as well as establishment a cooperation with other federal public organs at the Av. Perimetral for integrate the waste solid selective collection management